2021
DOI: 10.1371/journal.pone.0261586
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy and safety of second generation bipolar transurethral vaporization of the prostate (B-TUVP) for large benign prostate enlargement: Results from a retrospective feasibility study

Abstract: Background To investigate the efficacy and safety of a second-generation bipolar transurethral electro vaporization of the prostate (B-TUVP) with the new oval-shaped electrode for large benign prostatic enlargement (BPE) with prostate volume (PV) ≥100ml. Materials and methods 100 patients who underwent second-generation B-TUVP with the oval-shaped electrode for male lower urinary tract symptom (LUTS) or urinary retention between July 2018 and July 2020 were enrolled in this study. The patients’ characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Irrigation with normal saline was performed using a 26 Fr resectoscope, utilizing the transurethral resection in saline (TURis) system by Olympus and operating on cutting/coagulation settings at 200 W/120 W. After completing vaporization and coagulation, an 18 Fr three-way transurethral catheter was installed, only to be removed when hematuria had resolved (approximately on 2-4 POD). 3 Alternatively, HoLEP was performed using a 120 W holmium YAG laser (VersaPulse PowerSuite, Lumenis Surgical, San Jose, CA, USA) with a 550 nm end-ring ber (SlimLine, Lumenis). A 26 Fr continuous-ow resectoscope with saline irrigation was used.…”
Section: Operative Procedures Of B-tuvp and Holepmentioning
confidence: 99%
See 2 more Smart Citations
“…Irrigation with normal saline was performed using a 26 Fr resectoscope, utilizing the transurethral resection in saline (TURis) system by Olympus and operating on cutting/coagulation settings at 200 W/120 W. After completing vaporization and coagulation, an 18 Fr three-way transurethral catheter was installed, only to be removed when hematuria had resolved (approximately on 2-4 POD). 3 Alternatively, HoLEP was performed using a 120 W holmium YAG laser (VersaPulse PowerSuite, Lumenis Surgical, San Jose, CA, USA) with a 550 nm end-ring ber (SlimLine, Lumenis). A 26 Fr continuous-ow resectoscope with saline irrigation was used.…”
Section: Operative Procedures Of B-tuvp and Holepmentioning
confidence: 99%
“…Operative procedures of B-TUVP were described previously 3 . Brie y, under spinal or general anesthesia, the patient was placed in the lithotomy position and sterile draped.…”
Section: Operative Procedures Of B-tuvp and Holepmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous paper did not support the long-term advantage of TUVP over TURP for BPE treatment [ 3 , 4 ]. However, we have several reasons for performing B-TUVP instead of TURP including favorable learning curve, lower costs, better safety profile in anticoagulated patients on the basis of our previous papers [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we introduced the second-generation B-TUVP using an oval electrode (certification number: 29ABBZX00048000,26th Jun. 2017, Olympus, Japan) and demonstrated its efficacy and safety for large BPE (PV ≥ 100 ml) [ 5 ]. Our findings revealed that the second-generation B-TUVP facilitated more efficient vaporization owing to the wider surface of its oval electrode.…”
Section: Introductionmentioning
confidence: 99%